High-corrosion-resistance Al-Zr alloy double-layer anodic oxidation layer and preparation method thereof
By forming a double-layer anode oxidation layer on the surface of the Al-ZR alloy, the problem of poor oxidation layer in high temperature environment in high temperature environments is solved, and higher antioxidant and corrosion resistance is achieved, and the stability of the alloy is extended. Comparative time.
Patent Information
- Application Number
- CN202411575706.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-06
AI Technical Summary
It is difficult for existing anodizing technology to form an Al-Zr alloy oxide layer with good corrosion resistance and oxidation resistance under high temperature environments, resulting in a reduction in alloy stability.
The one-step aode oxidation treatment is adopted, and the crystal Al2O3 layer on the surface of the Al-ZR alloy is formed through a linear voltage, and an amorphous Al2O3 layer is formed on its surface. The regulatory voltage is maintained 600s to ensure the uniformity and density of the oxidation layer.
It significantly improves the antioxidant resistance and corrosion resistance of AL-ZR alloy under high temperature conditions, and enhances the stability and service time of the alloy.
Smart Images

Figure CN119372740A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material processing, and more specifically to a highly corrosion-resistant Al-Zr alloy double-layer anodized layer and a preparation method thereof. Background Art
[0002] Heat-resistant Al-Zr alloy has become the preferred material for high-voltage overhead transmission lines at home and abroad due to its excellent heat resistance, tensile strength and sag characteristics. However, the naturally grown oxide layer has extremely limited protection for the alloy in harsh service environments. The insufficient surface performance of Al-Zr heat-resistant alloy seriously limits its long-term stable service. Controlled pre-oxidation treatment improves the mechanical properties, corrosion resistance, friction properties and catalytic activity of the material surface in an efficient and economical way. Common methods for preparing aluminum alloy surface oxide layers include thermal oxidation, anodizing, chemical oxidation and micro-arc oxidation. Among them, anodizing directly converts the substrate surface into an oxide film by chemically reacting on the metal surface. Therefore, compared with the oxide deposition spraying method, the prepared oxide layer has the advantages of good adhesion to the alloy and relatively uniform thickness, and is widely used in the surface pretreatment of aluminum alloys.
[0003] The existing anodizing technology is to generate a single layer of anodized layer on the surface of the alloy, and its corrosion resistance and oxidation resistance are not ideal, especially in high temperature environments, where corrosion is very likely to occur, causing the stability of the alloy to decrease rapidly. In addition, the traditional anodizing technology is fixed voltage, and the instantaneous high voltage will cause the oxide film to be uneven and have too many defects.
[0004] Therefore, how to prepare Al-Zr alloy materials with corrosion resistance and oxidation resistance in high temperature environment while ensuring the stability of Al-Zr alloy materials has become a major technical problem that technicians in this field need to solve urgently. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned defects of the prior art, and to provide a highly corrosion-resistant Al-Zr alloy double-layer anodized layer and a preparation method thereof. By utilizing anodizing treatment, a one-step method is implemented to form a crystalline Al2O3 layer on the surface of the Al-Zr alloy and an amorphous Al2O3 layer on the surface of the crystalline Al2O3 layer. A linear boost is set to ensure that the initial voltage increases linearly, and the target voltage is maintained for 600s after being adjusted, thereby effectively improving the oxidation resistance of the Al-Zr alloy under high temperature conditions and the corrosion resistance in harsh environments. The amorphous Al2O3 layer can effectively hinder atomic diffusion and improve the stability of the Al-Zr alloy.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer comprises the following steps:
[0008] (1) grinding and polishing the Al-Zr alloy, ultrasonically cleaning the alloy with ethanol and acetone, and then sequentially alkali-washing, acid-washing, water-washing and drying to obtain a pretreated Al-Zr alloy;
[0009] (2) The pretreated Al-Zr alloy is used as an anode and a platinum wire is used as a cathode, and is immersed in an electrolyte solution at a temperature of 20°C to 30°C for anodization. The voltage is linearly increased from 0V to a target voltage of 50V to 200V at a linear increase rate of 1.67V / S to 6.67V / S, and maintained for 600s to form a crystalline Al2O3 layer on the surface of the pretreated Al-Zr alloy and an amorphous Al2O3 layer on the surface of the crystalline Al2O3 layer, thereby obtaining the Al-Zr alloy double-layer anodized layer.
[0010] Optionally, step (1) specifically includes:
[0011] The Al-Zr alloy is ground using SiC sandpaper with grain sizes of 1000, 1500, 2000, 2500 and 3000 to obtain a ground Al-Zr alloy;
[0012] The ground Al-Zr alloy is polished to a mirror finish using a diamond polishing paste and a silicon dioxide suspension to obtain a polished Al-Zr alloy;
[0013] The polished Al-Zr alloy was ultrasonically cleaned with acetone and ethanol in sequence, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then washed with water (18×10 6 Ωcm) alloy, and finally dried with compressed N2 gas and placed in a drying oven for 24h to obtain the pretreated Al-Zr alloy.
[0014] Optionally, in step (1), the particle size of the diamond polishing paste is 1.5 μm to 3.5 μm; and the particle size of the silicon dioxide in the silicon dioxide suspension is 20 nm to 50 nm.
[0015] Optionally, in step (2), the preparation of the electrolyte solution includes the following steps: using deionized water and citric acid particles to prepare a 0.1 mol / L citric acid solution, and using a 1 mol / L sodium hydroxide solution to adjust the pH of the citric acid solution to 5.8 to obtain the electrolyte solution.
[0016] Optionally, in step (2), the surface area of the platinum wire is 1.6 cm 2 .
[0017] Optionally, in step (2), the linear boost speed is 3.33V / S to 6.67V / S; and the target voltage is 100V to 200V.
[0018] Optionally, the Al-Zr alloy is Al-xZr, wherein x≤1 includes one of Al-0.2Zr, Al-0.5Zr and Al-1Zr alloys; preferably, Al-xZr is Al-0.2Zr, Al-0.5Zr or Al-1Zr alloy.
[0019] Optionally, the thickness of the crystalline Al2O3 layer is 15nm to 55nm; the thickness of the amorphous Al2O3 layer is 50nm to 200nm.
[0020] Optionally, the linear boost in step (2) can be controlled using LabView software.
[0021] The present invention also discloses a highly corrosion-resistant Al-Zr alloy double-layer anodized layer prepared by the above-mentioned preparation method, wherein the Al-Zr alloy double-layer anodized layer comprises a crystalline Al2O3 layer formed on the surface of the Al-Zr alloy and an amorphous Al2O3 layer formed on the surface of the crystalline Al2O3 layer.
[0022] Implementing the embodiments of the present invention will have the following beneficial effects:
[0023] Compared with the single oxide layer formed by traditional anodizing treatment, the preparation method provided by the present invention sets a linear boost to ensure that the initial voltage increases linearly, thereby avoiding the uneven oxide film and too many defects caused by instantaneous high voltage, and the Al-Zr alloy is anodized in a manner of maintaining the target voltage for 600s, so that a uniform and dense double-layer structure of a crystalline Al2O3 layer and an amorphous Al2O3 layer can be formed on the surface of the Al-Zr alloy, which can effectively improve the oxidation resistance of the Al-Zr alloy under high temperature conditions and the corrosion resistance in harsh environments; the amorphous Al2O3 layer can effectively hinder atomic diffusion, improve the stability of the Al-Zr alloy, and increase the service time; at the same time, the present invention is more sophisticated in the surface pretreatment of the Al-Zr alloy, and the preparation of the electrolyte solution is more scientific, thereby effectively reducing the surface defects of the oxide layer.
[0024] The present invention only needs one step of anodizing process to form a double-layer anodized layer on the surface of the Al-Zr alloy. The preparation process is simple and easy to control, and no high temperature and high pressure conditions are required. The raw materials are easily available and the cost is low, so it is suitable for industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1: Characteristic transient curves of the anodization process of Al-1Zr alloy. (a) Curve of current density changing with time during anodization, (b) Curve of voltage changing with time during anodization at different final voltages of 50 V (red), 100 V (blue), 150 V (green) and 200 V (purple).
[0026] Figure 2 : Scanning electron microscope (SEM) images of the surface of the anodized layer grown on Al-Zr alloy at (a) 50 V and (b) 200 V voltages.
[0027] Figure 3 : AES depth analysis images of (a) Al-0.2Zr, (b) Al-0.5Zr and (c) Al-1Zr alloys after anodization treatment at 200V.
[0028] Figure 4 : (a) Cross-sectional transmission electron microscopy (TEM) image of the anodized layer of Al-1Zr alloy grown at 200 V, (b) and (c) high-resolution images (HRTEM) of crystalline Al2O3 and amorphous Al2O3 oxide layers, respectively, and EDX elemental surface scanning image (d).
[0029] Figure 5 : Polarization test diagram of Al-1Zr alloy after anodizing in 3.5wt.% NaCl solution.
[0030] Figure 6 : Electrochemical impedance spectroscopy (EIS) diagrams of the Al-1Zr alloy after oxidation treatment in 3.5wt.% NaCl solution: (a) Nyquist plot; (b) and (c) Bode plots; (d) equivalent circuit diagram. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0032] Example 1
[0033] The Al-1Zr alloy ingot was cut into 15 mm × 15 mm × 5 mm blocks using wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit), and the samples were polished to mirror finish with diamond polishing paste (1.5-3.5 μm) and silica suspension (50 nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then alkaline washed and acid washed with deionized water (18 × 10 6The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2 Platinum wire was used as cathode in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (the pH regulator was a sodium hydroxide solution with a concentration of 1 mol / L) at a temperature of 25±5°C. The voltage was linearly increased from 0 V to a target voltage of 200 V within 30 s using LabView software, and then maintained at the target voltage of 200 V for 600 s (e.g. Figure 1 (b)), the corresponding current density is Figure 1 As shown in (a), the preparation of the double-layer anodized layer is completed when the oxidation time is over. The microscopic morphology of the oxide layer surface is as follows: Figure 2 (b) shows the microscopic morphology of the oxide layer cross section. Figure 4 As shown. Figure 4 TEM shows that there are two types of oxide layer structures: the oxide layer close to the substrate is crystalline, and the amorphous oxide layer is above the crystalline oxide layer. Figure 3 (c) AES depth analysis of the obtained oxide layer was performed to obtain the element content in the depth direction of the oxide layer, specifically the Al2O3 layer. The oxidized sample was subjected to polarization test and electrochemical impedance test in 3.5% NaCl solution. The test results are shown in Figure 5 and Figure 6 As shown, Figure 6 (d) The equivalent circuit also verifies the existence of a double-layer oxide film. Table 1 shows the Tafel fitting data of the polarization curve, and Table 2 shows the electrochemical impedance spectroscopy fitting data. From the test results and fitting data, it can be seen that the oxide layer after 200V anodization is the thickest, the corrosion potential is the highest, the current density is the lowest, and the corrosion resistance is the best.
[0034] Example 2
[0035] The Al-1Zr alloy ingot was cut into 15 mm × 15 mm × 5 mm blocks using wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit), and the samples were polished to mirror finish with diamond polishing paste (1.5-3.5 μm) and silica suspension (50 nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then alkaline washed and acid washed with deionized water (18 × 10 6 The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2Platinum wire was used as cathode, in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (pH adjuster was a sodium hydroxide solution with a concentration of 1 mol / L), at a temperature of 25±5°C, and the voltage was linearly increased from 0 V to a target voltage of 50 V within 30 s using LabView software, and then maintained at the target voltage of 50 V for 600 s (voltage as Figure 1 (b)), the corresponding current density is Figure 1 As shown in (a), the preparation of the double-layer anodized layer is completed when the oxidation time is over. The microscopic morphology of the oxide layer surface is as follows: Figure 2 (a) As shown. The oxidized sample was subjected to polarization test and electrochemical impedance test in 3.5% NaCl solution. The test results are shown in Figure 5 and Figure 6 As shown, Figure 6 (d) The equivalent circuit also verifies the existence of the double-layer oxide film. Table 1 shows the Tafel fitting data of the polarization curve, and Table 2 shows the electrochemical impedance spectroscopy fitting data. From the test results and fitting data, it can be seen that the oxide layer after 50V anodization is thinner, the corrosion potential is lower, the current density is higher, and the corrosion resistance is reduced, but it still has excellent corrosion resistance.
[0036] Example 3
[0037] The Al-1Zr alloy ingot was cut into 15 mm × 15 mm × 5 mm blocks using wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit), and the samples were polished to mirror finish with diamond polishing paste (1.5-3.5 μm) and silica suspension (50 nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then alkaline washed and acid washed with deionized water (18 × 10 6 The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2 Platinum wire was used as cathode, in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (pH adjuster was a sodium hydroxide solution with a concentration of 1 mol / L), at a temperature of 25±5°C, and the voltage was linearly increased from 0 V to a target voltage of 100 V within 30 s using LabView software, and then maintained at the target voltage of 100 V for 600 s (voltage as Figure 1 (b)), the corresponding current density is Figure 1 As shown in (a), the preparation of the double-layer anodized layer is completed after the oxidation time. The oxidized sample was subjected to polarization test and electrochemical impedance test in 3.5% NaCl solution. The test results are shown in Figure 5 and Figure 6 As shown, Figure 6 (d) The equivalent circuit also verifies the existence of the double-layer oxide film. Table 1 shows the Tafel fitting data of the polarization curve, and Table 2 shows the electrochemical impedance spectroscopy fitting data.
[0038] Example 4
[0039] The Al-1Zr alloy ingot was cut into 15 mm × 15 mm × 5 mm blocks using wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit), and the samples were polished to mirror finish with diamond polishing paste (1.5-3.5 μm) and silica suspension (50 nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then alkaline washed and acid washed with deionized water (18 × 10 6 The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2 Platinum wire was used as cathode, in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (pH adjuster was a sodium hydroxide solution with a concentration of 1 mol / L), at a temperature of 25±5°C, and the voltage was linearly increased from 0 V to a target voltage of 150 V within 30 s using LabView software, and then maintained at the target voltage of 150 V for 600 s (voltage as Figure 1 (b)), the corresponding current density is Figure 1 As shown in (a), the double-layer anodized layer is prepared after the oxidation time is over. The oxidized sample is subjected to polarization test and electrochemical impedance test in 3.5% NaCl solution. The test results are shown in Figure 5 and Figure 6 As shown, Figure 6 (d) The equivalent circuit also verifies the existence of the double-layer oxide film. Table 1 shows the Tafel fitting data of the polarization curve, and Table 2 shows the electrochemical impedance spectroscopy fitting data.
[0040] Example 5
[0041] The Al-0.5Zr alloy ingot was cut into 15 mm × 15 mm × 5 mm blocks using wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit), and the samples were polished to mirror finish with diamond polishing paste (1.5-3.5 μm) and silica suspension (50 nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then alkaline washed and acid washed with deionized water (18 × 10 6 The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2 Platinum wire was used as cathode, in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (pH adjuster was a sodium hydroxide solution with a concentration of 1 mol / L), at a temperature of 25±5°C, and the voltage was linearly increased from 0 V to the target voltage of 200 V within 30 seconds using LabView software, and then maintained at the target voltage of 200 V for 600 seconds. The preparation of the double-layer anodic oxide layer was completed when the oxidation time was over. TEM showed that there were two types of oxide layer structures, the oxide layer adjacent to the substrate was crystalline, and the amorphous oxide layer was above the crystalline oxide layer. Figure 3 (b) AES depth analysis of the obtained oxide layer is performed to obtain the element content in the depth direction of the oxide layer, specifically the Al2O3 layer, which has the thickest thickness.
[0042] Example 6
[0043] The Al-0.2Zr alloy ingot was cut into 15mm×15mm×5mm blocks by wire cutting. The wire cutting marks and surface oxide layer on the sample surface were ground with SiC sandpaper (1000, 1500, 2000, 2500 and 3000 grit). The samples were polished to mirror finish with diamond polishing paste (1.5-3.5μm) and silica suspension (50nm). After polishing, the samples were first ultrasonically cleaned in acetone and ethanol in turn, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil. After alkaline and acid washing, the samples were washed with deionized water (18×10 6 The alloy was rinsed with compressed N2 gas and dried in a drying oven for 24 hours. The pretreated Al-Zr alloy was used as the anode with a surface area of 1.6 cm 2Platinum wire was used as cathode in a citric acid solution with a pH of 5.8 and a concentration of 0.1 mol / L (the pH adjuster was a sodium hydroxide solution with a concentration of 1 mol / L), at a temperature of 25±5°C. LabView software was used to control the voltage to increase linearly from 0 V to a target voltage of 200 V within 30 s, and then the target voltage of 200 V was maintained for 600 s. When the oxidation time was over, the preparation of the double-layer anodic oxide layer was completed. Figure 3 (a) is the AES depth analysis of the obtained oxide layer, and the element content in the depth direction of the oxide layer is obtained, specifically the Al2O3 layer, which has the thinnest thickness.
[0044] Table 1 Fitting parameters of electrochemical impedance spectroscopy of Al-1Zr alloy after anodization
[0045]
[0046] Table 2 Fitting parameters of polarization test of Al-1Zr alloy after anodization.
[0047]
[0048] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer, characterized in that: The following steps are involved: (1) grinding and polishing the Al-Zr alloy, ultrasonically cleaning the alloy with ethanol and acetone, and then sequentially alkali-washing, acid-washing, water-washing and drying to obtain a pretreated Al-Zr alloy; (2) The pretreated Al-Zr alloy is used as an anode and a platinum wire is used as a cathode, and the alloy is immersed in an electrolyte solution at a temperature of 20°C to 30°C for anodization. The voltage is linearly increased from 0V to a target voltage of 50V to 200V at a linear increase rate of 1.67V / S to 6.67V / S, and maintained for 600s to form a crystalline Al2O3 layer on the surface of the pretreated Al-Zr alloy and an amorphous Al2O3 layer on the surface of the crystalline Al2O3 layer, thereby obtaining the Al-Zr alloy double-layer anodized layer.
2. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: Step (1) specifically includes: The Al-Zr alloy is ground using SiC sandpaper with grain sizes of 1000, 1500, 2000, 2500 and 3000 to obtain a ground Al-Zr alloy; The ground Al-Zr alloy is polished to a mirror finish using a diamond polishing paste and a silicon dioxide suspension to obtain a polished Al-Zr alloy; The polished Al-Zr alloy is ultrasonically cleaned with acetone and ethanol in sequence, then alkaline washed with 10% NaOH solution and acid washed with 10% HNO3 solution to remove oil, and then the alloy is washed with water, and finally dried with compressed N2 gas and placed in a drying oven for 24 hours to obtain the pretreated Al-Zr alloy.
3. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 2, characterized in that: In step (1), the particle size of the diamond polishing paste is 1.5 μm to 3.5 μm; the particle size of the silicon dioxide in the silicon dioxide suspension is 20 nm to 50 nm.
4. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: In step (2), the preparation of the electrolyte solution comprises the following steps: Deionized water and citric acid particles are used to prepare a 0.1 mol / L citric acid solution, and a sodium hydroxide solution with a concentration of 1 mol / L is used to adjust the pH of the citric acid solution to 5.8 to obtain the electrolyte solution.
5. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: In step (2), the surface area of the platinum wire is 1.6 cm 2 .
6. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: In step (2), the linear boost speed is 3.33V / S to 6.67V / S; and the target voltage is 100V to 200V.
7. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: The Al-Zr alloy is Al-xZr, wherein x≤1.
8. The method for preparing a highly corrosion-resistant Al-Zr alloy double-layer anodized layer according to claim 1, characterized in that: The thickness of the crystalline Al2O3 layer is 15nm-55nm; the thickness of the amorphous Al2O3 layer is 50nm-200nm.
9. A highly corrosion-resistant Al-Zr alloy double-layer anodized layer prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The Al-Zr alloy double-layer anodized layer includes a crystalline Al2O3 layer formed on the surface of the Al-Zr alloy and an amorphous Al2O3 layer formed on the surface of the crystalline Al2O3 layer.
Citation Information
Patent Citations
Aluminum alloy anode oxidation method
CN107641826A
Oxalic acid anodic oxidation process method for hard aluminum alloy shell part
CN113981500A
Method of manufacturing alumina porous structure
JP2008038237A